PHYSICAL AND NON-PHYSICAL INFRASTRUCTURE DEVELOPMENT LEVERAGE HUMAN DEVELOPMENT IN PAPUA PROVINCE - Eva Wany; Sarah Yuliarini; Budi Prayitno (STIE Mahardhika, 2022)
Poverty is a picture of the conditions of people who are unable to meet basic needs according to applicable standards. Some of the ways that the government has prepared to alleviate poverty, one of which is by developing infrastructure development. The aim of the study was to find out whether the development of physical infrastructure (electricity and roads) and non-physical infrastructure such as financial institutions (post offices) had an influence on poverty levels in the province of Papua with 10 Districs in 2017-2019. The data analysis technique implied the panel data consisting of cross section data and time series data. The results of this study showed that physical infrastructure has a significant influence while non-physical infrastructure has no significant effect on poverty rates in papua province.